Ecclesiast: A Novel Exploring Atheist Morality & Discrimination in Indonesia - Cherine Angelica Limina; Dwi Setiawan (Kata Kita: Journal of Language, Literature, and Teaching, 2022)
One of the many reasons why atheists are shunned is the common belief that lack of faith leads to a lack of moral foundation. However, analyses on the moral behaviors of atheists and religious people show that atheists behave similarly to any other group and that they possess their own methods of discovering a moral foundation. This thesis explores the discrimination atheists face within Indonesian society, and how atheists are able to develop and possess their own moral foundation. This thesis uses Turiel’s psychological Social Domain Theory, which is used to explain the moral panic around atheism as well as how morality develops outside of religious teaching. The creative work comes in the form of a magical realist novella about a young woman who slowly reconstructs her view on morality while on a journey to find God for an old corpse, guided by a mysterious archivist.